Aromatic diglycosides from Sophora tonkinensis and a multi-step conformer filtering procedure for TDDFT calculation of flexible glycoside. Issue 5 (4th May 2023) - Li, Xin; Yang, Sheng-Li; He, Hao-Ke; Zhang, Qian-Ru; Zhang, Ning; Wang, Su-Juan
Abstract: Three previously undescribed aromatic diglycosides (1, 5, and 8 ) and six known analogs (2–4, 6, 7, and 9 ) were isolated from the roots and rhizomes of Sophora tonkinensis Gagnep. Their structures were elucidated by detailed spectroscopic analysis. The absolute configuration of compound 8 was determined by comparing the experimental and TDDFT calculated ECD spectra of 8 and aglycone 8a . Furthermore, a multistep conformer filtering procedure for TDDFT calculation of flexible glycoside was proposed, which afforded high accuracy with acceptable computing cost in determining the absolute configuration of glycosides using quantum calculated ECD. Graphical Abstract: UF0001